THE USE OF EDUCATIONAL ACTIVITIES WITH BABIES: PERCEPTION OF PEDAGOGY STUDENTS - Cruz, Girlene de Albuquerque [UNESP]; Ricco Lucato Sigolo, Silvia Regina [UNESP]; Frigieri de Vitta, Fabiana Cristina [UNESP] (Fundacao Univ Tocantins, 2020)
This research aimed to verify and discuss the perception of pedagogy students about the initial training for the use of educational activities with babies. 937 students enrolled in six undergraduate courses at a public university in the State of Sao Paulo participated in the survey and answered a questionnaire on the topics: the role of training for performance with babies, perceptions about the use of activities of daily living, with toys, music and playground equipment. The data were analyzed using descriptive statistics. The results show a perception of the education of babies connected to the care of the working parents. However; they believe that the different activities can stimulate integral development, with highlight on toys and music and should be offered and planned by the teacher. It needs to improve the balance between theory and practice in initial teacher educational for this age group.
Keywords: Teacher training; Early childhood education; Nursery; Babies; Educational activities